DEVELOPMENT OF CREATIVITY OF ADOLESCENT SCHOOLCHILDREN IN MUSIC AND CREATIVE ACTIVITY (ON THE MATERIAL OF VARIOUS SINGING) - Стотика, О.; Чмир-Протасова, Г.О. (SWorldJournal, 2022)
The problem of formation and development of creative personality is relevant, because the multi-technological present requires non-standard problem solving, non-stereotypical decision-making, the introduction of innovative ideas. Under these conditions, t